Development of multi-residue analysis of herbicides in cereal grain by ultra-performance liquid chromatography–electrospray ionization-mass spectrometry. (1st February 2016) - Dong, Xinfeng; Liang, Shuxuan; Shi, Zhihong; Sun, Hanwen
Highlights: A sensitive method was developed for the determination of 50 herbicides in cereal grains by UPLC–ESI-MS. The response was linear over two orders of magnitude with a correlation coefficients ( r 2 ) over 0.992. The limits of quantification for the herbicides varied from 0.2 to 30 μg kg −1 . Analyzing soybean, corn and wheat samples from 17 counties evaluated this method. The method can be used for multi-class multi-residue analysis at low μg kg −1 level for the most herbicides. Abstract: A rapid and sensitive method was developed for the determination of 50 herbicides in cereal grain by ultra-performance liquid chromatography–electrospray ionization-mass spectrometry (UPLC–ESI-MS). Using acetonitrile effectively extracted 22 kinds of triazine and other basic herbicides, and using 90:10 v/v acetonitrile–phosphate buffer (pH = 7.5) effectively extracted other 28 herbicides. Chromatographic separation was achieved using gradient elution with acetonitrile–water as a mobile phase for 22 triazine and phenylurea herbicides and with 5 mM ammonium acetate aqueous solution containing 0.1% formic acid–acetonitrile as a mobile phase for other 28 herbicides. Using matrix-matched standard calibration curve effectively reduced the indirect matrix effects, ensured accurate quantification for these herbicides. The response was linear over two orders of magnitude with a correlation coefficients ( r 2 ) higher than 0.992. The limits of quantification for the herbicides varied from 0.2 to 25.6 μg kg −1 . The intra- and inter-day precisions (relative standard deviation, RSD) were 2.2–9.3% and 5.7–17.1%, respectively. The recovery varied from 61.6% to 110% with the RSD of 1.6–11.8%. Analyzing soybean, corn and wheat samples from 17 counties evaluated this method. The developed and validated method has high sensitivity, satisfactory recovery and precision, can ensure the multi-class multi-residue analysis at low μg kg −1 level for the most herbicides in cereal grain.